A natural compound harmine decreases melanin synthesis through regulation of the DYRK1A/NFATC3 pathway. Issue 1 (July 2021) - Park, Chi-Hyun; Kim, Goeun; Lee, Yuri; Kim, Haesoo; Song, Min Ji; Lee, Dong Hun; Chung, Jin Ho
Highlights: A natural compound harmine decreased melanin synthesis and tyrosinase expression in human MNT-1 melanoma cells and human primary melanocytes. Melanin synthesis was reduced by inhibition of DYRK1A, a harmine target, and enhanced by knockdown of NFATC3, a potential DYRK1A target. Harmine decreases melanin synthesis through regulation of the DYRK1A/NFATC3 pathway. Abstract: Background: Melanin plays important roles in determining human skin color and protecting human skin cells against harmful ultraviolet light. However, abnormal hyperpigmentation in some areas of the skin may become aesthetically unpleasing, resulting in the need for effective agents or methods to regulate undesirable hyperpigmentation. Objective: We investigated the effect of harmine, a natural harmala alkaloid belonging to the beta-carboline family, on melanin synthesis and further explored the signaling pathways involved in its mechanism of action. Methods: Human MNT-1 melanoma cells and human primary melanocytes were treated with harmine, chemical inhibitors, small interfering RNAs, or mammalian expression vectors. Cell viability, melanin content, and expression of various target molecules were assessed. Results: Harmine decreased melanin synthesis and tyrosinase expression in human MNT-1 melanoma cells. Inhibition of DYRK1A, a harmine target, decreased melanin synthesis and tyrosinase expression. Further studies revealed that nuclear translocation of NFATC3, a potential DYRK1A substrate, was induced via the harmine/DYRK1A pathway and that NFATC3 knockdown increased melanin synthesis and tyrosinase expression. Suppression of melanin synthesis and tyrosinase expression via the harmine/DYRK1A pathway was significantly attenuated by NFATC3 knockdown. Furthermore, harmine also decreased melanin synthesis and tyrosinase expression through regulation of NFATC3 in human primary melanocytes. Conclusion: Our results indicate that harmine decreases melanin synthesis through regulation of the DYRK1A/NFATC3 pathway and suggest that the DYRK1A/NFATC3 pathway may be a potential target for the development of depigmenting agents.